Transcending the Suffering in Cancer: Impact of a Spiritual Life Review Intervention on Spiritual Re-Evaluation, Spiritual Growth and Psycho-Spiritual Wellbeing - Lenneke Post; R. Ruard Ganzevoort; Irma M. Verdonck-de Leeuw (Religions, 2020)
In the confrontation with cancer, spiritual re-evaluation may help people to transform all-encompassing suffering into spiritual growth and psycho-spiritual wellbeing. The aim of this study was to examine whether spiritual life review (SLR), a semi-structured group narrative intervention that supports people with cancer to write and present their spiritual life story, is effective for the improvement of spiritual re-evaluation, spiritual growth, and psycho-spiritual wellbeing. In this mixed methods study, 57 cancer patients participated. Quantitative data were collected by means of patient reported outcomes (SAIL, Dutch Ryff, and NEIS) at baseline, post-intervention, and three and nine months follow-up (44 participants completed up to 9 months post-intervention). Changes over time were assessed via linear mixed model analysis (LMM). Qualitative data were collected by means of semi-structured interviews with 33 participants nine months post-intervention, and were coded in a two-stage process. Participating in SLR facilitated spiritual re-evaluation, and improved the course of spiritual growth, psycho-spiritual wellbeing, and ego-integrity. This study provides evidence that SLR is likely to improve spiritual re-evaluation, spiritual growth, and psycho-spiritual wellbeing after confrontation with cancer; it also suggests the importance of self-affirmation and ego-integrity for spirituality; and underscores the relevance of narrative spiritual interventions in the oncology setting.